Trust, distrust and the paradox of democracy - Piotr Sztompka (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1997)
According to the three-dimensional theory of trust which the author develops in his recent work, the measure of trust that people vest on their fellow citizens or institutions depends on three factors: the reflected trustworthiness as estimated by themselves in more or less rational manner, the attitude of basic trustfulness deriving from socialization, and the culture of trust pervading their society and normatively constraining for each member. The culture of trust is shaped by historical experiences of a society - the tradition of trust, and by the current structural context -the trust-inspiring milieu. The author presents a model of a structural context conducive for the emergence of the culture of trust, and then argues that the democratic organization contributes to the trust-generating conditions, like normative certainty, transparency, stability, accountability etc. The mechanism of this influence is found to be doubly paradoxical. First, democracy breeds the culture of trust by institutionalizing distrust, at many levels of democratic organization. And second, the strongest influence of democracy on the culture of trust may be expected when the institutionalized distrust remains only the potential insurance of trustworthiness, a resource used sparingly and only when there appear significant breaches of trust. Of all three components in the three-dimensional model of trust, the cultural dimension is most susceptible to practical, political measures. And the most promising method to elicit the culture of trust is designing democratic institutions and safeguarding their viable functioning.
Keywords: 300